2008
DOI: 10.1016/j.scitotenv.2008.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of dioxin-like, estrogenic and anti-androgenic activities in sediments of the Bizerta lagoon (Tunisia) by means of in vitro cell-based bioassays: Contribution of low concentrations of polynuclear aromatic hydrocarbons (PAHs)

Abstract: We used an array of in vitro cell-based bioassays to assess dioxin-like, estrogenic and (anti-)androgenic activities in organic extracts of sediments from the Bizerta lagoon, one of the largest Tunisian lagoons subjected to various anthropogenic and industrial pressures. The sediments were sampled both in winter and summer 2006 in 6 stations differently impacted and in one reference station located in the seawards entrance of Ghar el Melh lagoon. Chemical analyses of the 16 priority PAHs showed that the sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 48 publications
6
55
0
1
Order By: Relevance
“…Underestimated TEF values could partly explain the disparity between theoretical and practical genotoxic data for mixtures of PAHs (Rodriguez et al, 1997;Baird et al, 2005) and could result in an underestimation of risk. Nonetheless, our GEF values are similar to other published TEFs (Durant et al, 1996;Louiz et al, 2008;US-EPA, 2010) (Table 3), in particular for highly genotoxic and carcinogenic compounds DBahA (Nisbet and LaGoy, 1992), DMBA (Collins et al, 1998), and DBalP (Wynder and Hoffmann, 1961). For BcF, BghiP and IP, for which a limited number of available carcinogenesis data exist, a more important difference is observed between our equivalent factors and those reported by the US EPA (US-EPA, 2010).…”
Section: Genotoxic Equivalent Factor Determinationsupporting
confidence: 88%
See 1 more Smart Citation
“…Underestimated TEF values could partly explain the disparity between theoretical and practical genotoxic data for mixtures of PAHs (Rodriguez et al, 1997;Baird et al, 2005) and could result in an underestimation of risk. Nonetheless, our GEF values are similar to other published TEFs (Durant et al, 1996;Louiz et al, 2008;US-EPA, 2010) (Table 3), in particular for highly genotoxic and carcinogenic compounds DBahA (Nisbet and LaGoy, 1992), DMBA (Collins et al, 1998), and DBalP (Wynder and Hoffmann, 1961). For BcF, BghiP and IP, for which a limited number of available carcinogenesis data exist, a more important difference is observed between our equivalent factors and those reported by the US EPA (US-EPA, 2010).…”
Section: Genotoxic Equivalent Factor Determinationsupporting
confidence: 88%
“…1 and 2). The potency of BbF was also higher than BkF in terms of carcinogenicity (Wynder and Hoffmann, 1959), mutagenicity (Durant et al, 1996) and CYP induction (Louiz et al, 2008). Recently, RPFs of these compounds were revaluated, resulting in a value of 0.8 for BbF and 0.03 for BkF (US-EPA, 2010).…”
Section: Genotoxicity Of Pahs In Human Cell Linesmentioning
confidence: 99%
“…The 4-and 5-ring benz[a]anthracene and benzo[k]fluoranthene were principal AhR agonist activity contributors owing to their higher TEFs (7 and 11, respectively). Nonetheless, 9 AhR agonistic PAHs only accounted for a small portion of the AhR agonist activities in indoor dust (2.1-6.2%), which were similar to other studies (Louiz et al, 2008;Muusse et al, 2012;Tue et al, 2013). Our results indicated that further investigation is necessary to identify unknown xenobiotic AhR agonist contaminants in indoor dust from Taiwan.…”
Section: Contributions Of Pahs To the Ahr Agonist Activity In Indoor supporting
confidence: 88%
“…Significant correlation could not be found among total PAH content, AhR agonist activity, AR antagonist activity, and genotoxic activity, whereas samples with higher PAH contents, such as indoor dust from photocopy room, computer room, and laboratory also elicited stronger AhR agonist activities (Table 1). In addition, although several PAHs have been shown to exhibit AhR agonist, AR antagonist, and genotoxic potencies, their contributions to AhR agonist and AR antagonist activities in diesel exhaust particles or sediment have been reported to be low (Kizu et al, 2003;Louiz et al, 2008). Also, the contribution of genotoxic PAH metabolites formed via metabolic activation may be insignificant since the genotoxicity tests were performed without S9 activation in this study .…”
Section: Contents Of Pahs In Indoor Dust Samplesmentioning
confidence: 73%
“…The overwhelming majority of documents in the list of most cited documents were articles except one document which was a review article (Al-Yousuf et al 2000;Baveye et al 1999;El-Fadel and Massoud 2000;Elminir 2005;Khan et al 2011;Louiz et al 2008;Loutfy et al 2006;Nawar and Doma 1989;Qadir and Oster 2004;Rocher et al 2004;Romeo et al 1999). The citation rates for these documents range from 57 to 202.…”
Section: Resultsmentioning
confidence: 99%